Tanggungjawab Yuridis Hak Pengelolaan Lingkungan Akibat Aktivitas Pemurnian Nikel - Nashriany Jufri, Nur (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2024)
This study aims to analyze the legal responsibility of PT. Virtue Dragon Nickel Industrial Park (VDNIP) for the right to a good and healthy environment and the forms of accountability of PT. VDNIP in realizing such an environment in Morosi District, Konawe Regency. This research employs a normative legal method with a case study approach involving legal products, including the review of legislation. Based on the research findings, the right to a good and healthy environment must be balanced with the obligation to maintain environmental functions and control pollution. This balance reflects that the community plays a crucial role in preserving environmental sustainability. A good and healthy environment cannot be achieved if the community remains passive towards environmental management. Therefore, in accordance with the provisions of Law Number 32 of 2009, the community must actively participate in environmental protection and management. The research results indicate that the responsibility of PT. VDNIP in maintaining a good and healthy environment heavily relies on the active participation of the community in monitoring and managing the environment.